АВС-XYZ-ANALYSIS IN THE MANAGEMENT OF RECEIVABLES OF THE ENTERPRISE - STEFANOVYCH, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines topical issues of application of ABC and XYZ analysis in the management of accounts receivable of an enterprise. The purpose of the article is to select criteria for conducting ABC-XYZ analysis of accounts receivable to assess the credit rating of buyers and apply appropriate debt collection methods for each group of debtors. The study found that accounts receivable is a form of commodity lending, and its volume significantly affects the financial condition of an enterprise. The article considers topical issues of accounts receivable management at enterprises in modern conditions as a prerequisite for strengthening payment discipline. The essence of ABC-analysis as one of the mathematical and statistical methods of analysis used for management purposes is investigated. The advantages and weaknesses of ABC analysis are identified. It is proved that for the formation of the credit policy of enterprise, to determine the credit rating of debtors, it is advisable to choose such parameters of ABC analysis as sales volume, terms of delay in payments and the amount of overdue receivables in absolute and relative terms. The credit rating of customers using the ABC analysis is built. A matrix of the combined results of ABC and XYZ analysis is presented, where nine groups of debtors are allocated, each of which requires the development of its own management technology. The main groups of methods of debt collection from debtors have been identified, the use of which will help to reduce the risk of non-payment of debts by buyers and will help to establish an effective credit policy at the enterprise. Further research should be aimed at expanding the methodological tools for managing the accounts receivable of an enterprise.
Keywords: accounts receivable; management; ABC-XYZ analysis; credit rating